Diversity and Ecology of Sand Flies (Diptera: Psychodidae), Potential Vectors of Leishmania in the Quang Ninh Province, Vietnam. Issue 1 (26th July 2019) - Vu, Nam Sinh; Tran, Son Hai; Tran, Phong Vu; Tran, Tu Cong; Tran, Duong Nhu; Dang, Anh Duc; Nguyen, Yen Thi; Vu, Lieu Thi; Ngo, Phuong Khanh; Nguyen, Hoang Viet; Cassan, Cécile; Nguyen, Chau Van; et al.
Abstract: The study aims to make an update on the distribution and ecology of sand flies in the Quang Ninh province, Northern Vietnam, where Leishmania cases were reported in 2001. Seventeen sites were chosen in three districts of the province: Ha Long, Cam Pha, and Hoanh Bo. Phlebotomine sand flies were collected using 68 CDC light traps from May 30 to 3 June 2016. Captured specimens were transferred individually into Eppendorf tubes with 90% ethanol. The sand fly heads and genitalia were removed and were mounted in Euparal after successive different baths. Specimen identification was determined based on the morphology of the cibarium, pharynx, and/or male genitalia or female spermathecae. A total of 416 sand flies (125 females, 283 males) belonging to four genera were collected and 10 sand fly species were identified: Sergentomyia silvatica, Se. barraudi, Se. hivernus, Se. bailyi, Phlebotomus mascomai, Ph. stantoni, Ph. yunshengensis, Ph. betisi, Chinius junlianensis, Idiophlebotomus longiforceps . The Sergentomyia genus prevailed (79.7% of the collected sand flies), followed by the Phlebotomus genus (13.7%), the Chinius genus (6.1%), and the Idiophlebotomus genus (0.8%). Besides these well-defined taxa, five specimens, named sp1, showed unknown morphological characteristics, requiring further study. The majority of sand flies were collected in rock caves suggesting the cavernicolous character of the species in the Quang Ninh province. However, specimens were also collected in intra and peridomiciliary sites in which Ph. stantoni and Se. hivernus were found as the main species. It is worth noting that two Ph. stantoni were found in the house of a patient affected by Leishmania .